A New Approach to Operations on Bipolar Neutrosophic Soft Sets and Bipolar Neutrosophic Soft Topological Spaces - Taha Yasin Ozturk (Neutrosophic Sets and Systems, 2019)
In this study, we re-define some operations on bipolar neutrosophic soft sets differently from the studies [2]. On this operations are given interesting examples and them basic properties. In the direction of these newly defined operations, we construct the bipolar neutrosophic soft topological spaces. Finally, we introduce basic definitions and theorems on bipolar neutrosophic soft topological spaces